Neon signs in urban space, yesterday and today. A case study based on Lublin - Chęć-Małyszek, Agnieszka (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2022)
During the communist era, neon signs were something Poland could boast of. At that time, the streets were drowning in luminous advertising, which was impossible not to notice. Recent years have brought disastrous quality of urban advertising and the prevailing arbitrariness has contributed to the degeneration of urban spaces. Colourful neon signs once prevailed in Polish streets, serving as a model example of advertising whose impact was crucial in the perception of urban space. Today, neon signs are considered works of art, and the most valuable achievement of Polish 20th century design, which we can mainly admire today in museums. In the last decade, we have been reminded of their existence and efforts have been made to save them and return them to urban spaces. The purpose of the article is to draw attention to the extraordinary value of neon signs as an important building block of urban space and to highlight their artistic and social functions. The undertaken research includes material on neon signs from the communist era as well as those newly designed, based on the city of Lublin.